Does technical drawing increase students' mental rotation ability? - Ogunkola, Babalola; Knight, Carlos (Cogent education, 2018)
In this article, we examined whether technical drawing increased the mental rotation ability in 13- to 15-year-old students (N = 201). Students were pretested with the Mental Rotations Test. Later, a group of students was exposed to technical drawing for 10 weeks, which involved specific training with spatial activities and tasks, to increase mental rotation ability. The other group followed their normal classes. Then both groups were posttested and scores showed that the technical drawing students significantly outperformed the control group with a moderate effect size. Additional analyses revealed that the technical drawing students' scores increased from pretest to posttest, with a similar performance in the control group. But this research suggested technical drawing increased students' mental rotation ability with greater effectiveness than other subject areas that may also have broad spatial activities and tasks. Additionally, those other subjects employ classical and often static methods which may or may not provide spatial training that is either effective or efficient compared to technical drawing.